Adult picky eating and associations with childhood picky eating, maternal feeding, aversive sensory responsiveness, disgust and obsessive-compulsive symptoms - Zohar,Ada H.; Barhum Shapira,Dorin; Lev-Ari,Lilac; Bachner-Melman,Rachel (PeerJ, 2025)
Background Adult picky eating (PE) can cause distress, malfunction, and malnutrition. The purpose of this study was to examine adult PE, its relationship to childhood PE and to symptoms of obsessive-compulsive disorder (OCD), sensory processing disorder, food and general disgust, and maternal child feeding practices. Methods Adult participants (N = 772; 636 women) self-reported on measures of adult PE (Adult Picky Eating Questionnaire (APEQ)), obsessive-compulsive symptoms (Obsessive-Compulsive Inventory–Revised (OCI-R)), sensory processing difficulties (Sensory Responsiveness Questionnaire–Intensity Scale (SRQ-IS)), general disgust propensity (Disgust Propensity and Sensitivity Scale-12 (DPSS-12)), food disgust (Food Disgust Scale–short (FDS-S)), and three maternal feeding practices (Retrospective Child Feeding Questionnaire (RCFQ)). Results Childhood PE and current adult PE were strongly associated. Adults with PE who scored in the top 25 percentile on the APEQ were at risk for OCD and sensory processing disorder; most reported having been picky eaters in childhood. Structural equation modelling with good fit indices confirmed a developmental model in which general disgust, food disgust and sensory processing difficulties contributed to childhood PE and maternal feeding practices (pressure to eat, restriction), which in turn contributed to OCD symptoms. In addition, pressure to eat, restriction and OCD symptoms contributed directly to adult PE. Conclusions Severe adult PE is related to childhood PE and disgust sensitiviy, OCD and sensory processing disorder. Adults with severe PE may meet criteria for adult avoidant restrictive feeding or eating disorders. For adults with extreme PE clinical intervention may be warranted.
Keywords: Picky eating; Aversive sensory responsiveness; Disgust; Obsessive-compulsive disorder; Parental feeding practices